Determining terminal concession durations in seaports: theoretical considerations, applicable techniques and current practices - Christophe Theys; Theo Notteboom (Journal of International Logistics and Trade, 2010)
The awarding of terminals to private operators is considered a prime task of landlord port authorities. Yet, terminal concessions in seaports have only recently gained interest in academic circles. The awarding process poses a complex set of managerial challenges to port authorities, one of the key issues being the determination of the duration of the concession. Despite the importance of the duration of terminal concessions in seaports, the issue has not received much attention in academic circles. Factors impacting on the duration of contracts, leases or concessions have, however, been studied extensively in other research areas, such as agriculture, coal contracts, franchising and natural gas. This paper uses insights from these academic studies to obtain a better understanding of the impact of concession duration on the stakeholders involved and relates them to empirical evidence on concession length in European seaports. The paper then proposes a classification scheme for the exogenous determination of concession duration, based on techniques developed for Public-Private-Partnerships in large infrastructure projects. In the last section the paper discusses the importance of concession durations to various stakeholders in seaports and illustrates these principles using a case study.